Optimalization Family Health Task in Adolescent Reproductive Health Through Familly Support Group at Jenggawah Village - maurida, nurul; Ali Basri, Achmad; Angelia Silvanasari, Irwina; Vitaliati, Trisna (Community Development Journal, 2024)
Reproductive health problem among adolescent are increases, such as child marriage, premarital sexual behavior, sexual violence, use drugs and cigarettes, balanced nutrition and access to health services. Adolescents in rural areas dominate reproductive health problems among adolescents. The family was contributing to adolescent decision to act. The objective were to improve family health maintenance task in adolescent reproductive health using family support group (FSG) method. The family support group involving 20 families with 2 meetings, that are increasing knowledge at meeting 1 and implementing FSG at meeting 2. Before and after the FSG was carried out, participants were given the opportunity to fill out a questionnaire about family health maintenance tasks. The results of this community service was increases implementation of family health maintenance tasks in improving reproductive health in adolescents. The majority of families' ability to recognize problems has increased by 85% in the good category, the majority of families' ability to make decisions has increased by 100% in the good category, families' ability to care for the family has increased by 65% in the good category, families' ability to modify the environment experienced an increase of 70% in the good category and families' ability to access health services increased by 90% in the good category. Family support groups can be one method applied to improve adolescent reproductive health through optimizing family health maintenance tasks.